Cannabis Smoking-induced Diffuse Alveolar Hemorrhage - Alqahtani, Ali (Cureus, 2019)
Cannabis smoking is common among adolescents and young adults. Diffuse alveolar hemorrhage (DAH) is a rare and life-threatening complication of cannabis abuse. DAH is characterized by bleeding into alveoli secondary to the disruption of the alveolar-capillary basement membrane as a result of an injury at the level of alveolar microcirculation. The differential diagnosis of DAH includes systemic vasculitis, bland pulmonary hemorrhage, and alveolar damage. The impact of cannabis on the respiratory function includes mucus hypersecretion, inflammatory edema, and increased alveolar permeability. Moreover, in vitro coagulation studies on rats showed that two major cannabinoids, cannabinol and THC, have antithrombotic activity. We present two cases of cannabis use resulting in acute lung injury and diffuse alveolar hemorrhage.